Mechanism Design with Communication Constraints - Mookherjee, Dilip; Tsumagari, Masatoshi (Journal of Political Economy, 2014)
We consider mechanism design in which message sets are restricted owing to communication costs, preventing full revelation of information. A principal contracts with multiple agents each supplying a one-dimensional good at a privately known cost. We characterize optimal mechanisms subject to incentive and communication constraints, without imposing arbitrary restrictions on the number of communication rounds. We show that mechanisms that centralize production decisions are strictly dominated by those that decentralize decision-making authority to agents, and optimal communication mechanisms maximize information exchanged directly among agents. Conditions are provided for these to involve gradual release of information over multiple rounds either simultaneously or sequentially.